A Strategy for Content Personalization in Virtual Reality Systems - Melo, Gabriel Vieira; Silva, Alexandre Carvalho; Cardoso, Alexandre; Lamounier, Edgard A.; Sousa, Ligia Christine Oliveira; Lima, Diogo A. C. de; Ferreira, Angel Rodrigues (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
With technological advancement and the increasing integration of new technologies, Virtual Reality (VR) has been gaining ground across various industrial and operational processes, being applied in training, simulations, and operations monitoring. However, challenges such as high costs, lack of specialized teams, and difficulties in adapting and creating new features after implementation can compromise its effectiveness. Since much of the functionality in these environments is defined at the time of creation, there are limitations in meeting new demands from end users. In this context, this project proposes an accessible integrative architecture that enables dynamic customization of VR environments across different applications. As a case study, the electric substation sector was chosen to demonstrate its applicability in planning, training, and maintenance, illustrating the potential to expand VR use in diverse scenarios. The developed solution allows content to be adapted according to the specific needs of the application, enabling component data within the scene to be modified intuitively and efficiently. Thus, the project aims to make VR environment customization practical and accessible, eliminating the need for manual adjustments by specialized teams and making the process more scalable and effective.